2017
DOI: 10.1016/j.socscimed.2016.12.036
|View full text |Cite
|
Sign up to set email alerts
|

Is it time to talk? Understanding specialty child mental healthcare providers' decisions to engage in interdisciplinary communication with pediatricians

Abstract: Communication between pediatric mental health and primary care providers is often inconsistent and frequently rated as unsatisfactory by providers of both disciplines. While numerous studies report pediatricians’ desire for increased feedback from mental health providers, less is known about mental health providers’ perspectives on collaborative communication with pediatricians. In the current qualitative study, 9 practitioners at 2 mental health practices participated in interviews about their experiences rel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 34 publications
1
2
0
Order By: Relevance
“…The findings build on previous studies exploring factors impacting on teamworking found in more stable healthcare settings. Themes such as the influence of leadership, communication and the importance of learning together reinforce earlier studies, 15,34 and the practical considerations 16 for the organizational factors affecting teamworking. The need for roles to expand and scope of practice to be extended has been identified in clinical practice previously, for example, extended scope physiotherapists (ESPs) in musculoskeletal care 35 (eg, requesting X-rays) and pharmacists in chronic pain clinics 36 (eg, prescribing medication).…”
Section: Discussionsupporting
confidence: 59%
See 1 more Smart Citation
“…The findings build on previous studies exploring factors impacting on teamworking found in more stable healthcare settings. Themes such as the influence of leadership, communication and the importance of learning together reinforce earlier studies, 15,34 and the practical considerations 16 for the organizational factors affecting teamworking. The need for roles to expand and scope of practice to be extended has been identified in clinical practice previously, for example, extended scope physiotherapists (ESPs) in musculoskeletal care 35 (eg, requesting X-rays) and pharmacists in chronic pain clinics 36 (eg, prescribing medication).…”
Section: Discussionsupporting
confidence: 59%
“…The authors declare there is no conflict of interest. A commitment to working collaboratively, 34,35 designing team based job designs 36 2. Understanding the significance of teamworking in a dynamic setting 3.…”
Section: Conflict Of Interestmentioning
confidence: 99%
“…Regular consultation between medical providers and mental health professionals is now considered a standard of care for youth with diabetes. However, a qualitative study found that mental health professionals typically initiate consultation with pediatricians on a case-by-case basis rather than systematically (Reiss et al, 2017), in line with participants’ observations that they rarely hear from mental health providers outside of the clinic.…”
Section: Discussionmentioning
confidence: 70%